Economics as a Field of Research - Young, Allyn A. (Quarterly Journal of Economics, 1927)
I. The social sciences differ from the physical in that the observer's interest lies within them, 1. — The contractual and the institutional views of society, 5. — Corresponding types of investigation, 6. — The genetic point of view, 7. — II. Group research and its promise, 11. — Induction and deduction, 12. — Fruitful hypotheses essential, 14. — Individual research; the constructive imagination, 15. — Promising types of research, 16. — The limitations and promise of research, 23.